Numerical investigation of secondary peaks in Nusselt profile under water jet impingement - Siddiqui, Umair; Ansari, Emad; Khan, Sher Afghan; Patil, Rajesh (American Institute of Aeronautics and Astronautics, 2020)
In the present work, numerical simulations were conducted to observe the occurrence of secondary peaks in Nusselt profiles, which were generated on the target surface due to the impingement of water. Simulations were carried out in an ANSYS CFX solver by varying the Reynolds number Re from 825 to 41,292 and the nozzle-target spacing (Z∕d) from 0.25 to 4. A k-ε turbulence model with realizable equations having an optimum grid size (minimum face size of 0.0008575 and number of elements of 1,225,616) was incorporated. This computational domain with the mentioned grid size was subjected to various boundary conditions (for plotting the Nusselt profile for different impinging and geometric parameters). It was found that the high velocities of jets with lower nozzle-target spacings were the leading causes for the occurrence of secondary peaks in the Nusselt profile. A nondimensional constant was defined as the ratio of the Reynolds number to the nozzle-target spacing, carrying a threshold magnitude above which secondary peaks in Nusselt profiles were bound to happen. The value of this nondimensional constant Re∕Z∕d was approximated to 1000. The occurrence of an intermediate transition region due to the imbalance penetrating momentum was the true cause of the occurrence of secondary peaks. This was justified using velocity contours.